Chotro. Learning from the Indigenous - Geoffrey Vernon Davis (Universitat Autònoma de Barcelona, 2019)
The Chotro project was established jointly by the Bhasha Research and Publication Centre in Baroda and the European Association for Commonwealth Literature and Language Studies (EACLALS). Founded initially to document the linguistic, literary, and artistic heritage of tribal communities, Bhasha has established an academy for the promotion of tribal studies and the education of the marginalised tribal people of India, the adivasis. Chotro, which emerged from these activities, aimed to situate adivasis in the context of indigenous peoples across the world with whom they have much in common but little, if any, contact. Conceived as a cross-cultural, interdisciplinary forum, Chotro ‘brought together’ – for that is the meaning of the word in the Bhil language  ̶  indigenous people from India and elsewhere with activists and scholars from many countries working in such diverse fields as anthropology, sociology, literature, linguistics, history, music, museum studies, and human rights. Four Chotro gatherings were convened which addressed marginalisation, social deprivation, lack of access to education, loss of traditional lands, knowledge systems, oral traditions, endangered languages, and the representation of the indigenous in performance and the visual arts. Chotro thus illustrated one way in which scholars may contribute to social and cultural activism.